Chemical composition of the lipophilic compounds from the rind and pith of papyrus (Cyperus papyrus L.) stems - Rosado, Mario J.; Marques, Gisela; Rencoret, Jorge; Gutiérrez, Ana; Bausch, Florian; Rosenau, Thomas; Potthast, Antje; del Río, José C. (Frontiers in Plant Science, 2022)
Papyrus (Cyperus papyrus L.) is a sedge plant with a high rate of biomass productivity that represents an interesting raw material to produce chemicals, materials and fuels, which are currently still obtained from fossil resources, in the context of a lignocellulosic biorefinery. In this work, the content and chemical composition of the lipids present in papyrus stems were thoroughly studied. For this, the papyrus stems were separated into the rind and the pith. The lipid content accounted for 4.1% in the rind and 4.9% in the pith (based on dry matter). The main compounds identified in both parts of the papyrus stem were hydrocarbons, n-fatty acids, 2-hydroxyfatty acids, alcohols, alkylamides, mono- and diglycerides, steroids (sterols, ketones, hydrocarbons, esters and glycosides), tocopherols, tocopherol esters, phytol, phytol esters, alkyl ferulates, ω-carboxyalkyl ferulates (and their monoglycerides), and acylglycerol glycosides. The rind presented a predominance of n-fatty acids (6790 mg/kg; that represented 28.6% of all identified compounds), steroid compounds (6255 mg/kg; 26.3%), phytol and phytol esters (4985 mg/kg; 21.0%), and isoprenoid hydrocarbons, namely phytadiene and squalene (2660 mg/kg; 11.2%), while the most abundant lipids in the pith were steroids (8600 mg/kg; 44.4% of all identified compounds) and fatty acids (6245 mg/kg; 32.2%). Due to the great diversity and significant abundance of the compounds identified in papyrus, it can be considered as a potential raw material for biorefineries to obtain valuable phytochemicals of interest to various industrial sectors.